2018
DOI: 10.1016/j.jpba.2017.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Accurate quantification of PGE2 in the polyposis in rat colon (Pirc) model by surrogate analyte-based UPLC–MS/MS

Abstract: An accurate and reliable UPLC-MS/MS method is reported for the quantification of endogenous Prostaglandin E2 (PGE) in rat colonic mucosa and polyps. This method adopted the "surrogate analyte plus authentic bio-matrix" approach, using two different stable isotopic labeled analogs - PGE-d9 as the surrogate analyte and PGE-d4 as the internal standard. A quantitative standard curve was constructed with the surrogate analyte in colonic mucosa homogenate, and the method was successfully validated with the authentic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The average RF value was 0.88 (see Equation ), which did not equal 1. Possible reasons for the response difference included ionization difference, gas‐phase hydrogen/deuterium scrambling, inaccurate purity characterization, kinetic isotope effect, and stable‐isotope‐labeled analyte distribution . Therefore, we calculated the concentration of acetic acid using the RF value and the calibration curve of the surrogate analyte (see Equations and for details).…”
Section: Resultsmentioning
confidence: 99%
“…The average RF value was 0.88 (see Equation ), which did not equal 1. Possible reasons for the response difference included ionization difference, gas‐phase hydrogen/deuterium scrambling, inaccurate purity characterization, kinetic isotope effect, and stable‐isotope‐labeled analyte distribution . Therefore, we calculated the concentration of acetic acid using the RF value and the calibration curve of the surrogate analyte (see Equations and for details).…”
Section: Resultsmentioning
confidence: 99%
“…The PGE 2 was quantitated using the validated method published by us previously with modification. 18 Briefly, a 50 μL aliquot of cell medium and 10 µL d4-PGE 2 (as the internal standard, final concentration was 20ng/mL) were mixed with 500 μL of ethyl acetate for liquid–liquid extraction. Then, 400 µL supernatant was transferred from the mixture after vortex and centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Several studies also found that celecoxib treatment significantly reduced the tumor multiplicity in the colon in Pirc rats (Pirc, F344/NTac-Apc am1137 ), which has similar biology that closely models human FAP characteristics. 17,18 However, it has been proven in humans that systemic inhibition of COX-2 for a prolonged period of time caused significant and sometimes deadly adverse effects because COX-2 is constructively expressed in some tissues including the cardiovascular system. 19,20 Evidence in support of COX-1 being "good" for our health is that PGE 2 derived from COX-1 is mainly involved in homeostatic functions throughout the body.…”
mentioning
confidence: 99%
“…We have previously studied the epigenetic mechanism of action of 3,3′- Diindolylmethane (DIM) in colon cancer [ 10 ]. DIM is a natural chemopreventive compound that is formed from indol-3-cabinol (I3C) and has been reported to have various anti-cancer mechanisms in CRC [ 11 , 12 , 13 , 14 , 15 , 16 ]. DIM can be found in cruciferous vegetables such as broccoli, Brussels sprouts, cabbage and kale.…”
Section: Introductionmentioning
confidence: 99%